The Interaction between Opening Call Auctions and Ongoing Trade: Evidence from the NYSE - Brooks,Raymond; Moulton,Jonathan (Review of Financial Economics, 2004)
We investigate the impact that the opening batch has on trading for the remainder of the day and what impact the prior day's trading has on the subsequent day's open. Traders have an interest in these trading impacts as their trades may cluster around opening and closing time periods. We find that the larger the volume in the opening batches, the greater the volume across the day. We also find the prior day's volume being positively related to the subsequent day's opening volume. Combined, these results suggest a continuing pattern of trade volume rolling from one day to the next. Additionally, we find that the spread in the continuous market can be partially attributed to the price change in the opening batch. We also find evidence of opening trade price reversals. Combined with the absence of price reversals following the opening trade, we conclude that the opening process may be more efficient at handling information than the continuous market.
Keywords: Finance